Positive pole piece, preparation method thereof and battery

By adding porous carbon to the first active material layer of the positive electrode sheet, the problem of poor circulation performance caused by decomposition of lithium-ion batteries for lithium replenishment is solved, and more efficient lithium ion conduction and better battery circulation performance is achieved. .

CN119480914APending Publication Date: 2025-02-18EVE POWER CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411732054.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

During the first charging process, lithium-ion batteries are decomposed and produced by gas, resulting in poor battery circulation performance.

Method used

Porous carbon is added to the first active material layer of the positive electrode sheet to promote the dispersion of lithium supplement agent and gas export, and improve the porosity and lithium ion conduction efficiency of the positive electrode sheet.

Benefits of technology

Through the use of porous carbon, the damage to the interface of the positive electrode sheet by the lithium supplement gas production is alleviated, the transmission efficiency of lithium ions in the positive electrode sheet is improved, and the circulation performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480914A_ABST
    Figure CN119480914A_ABST
Patent Text Reader

Abstract

The invention provides a positive pole piece, a preparation method thereof and a battery, and aims to solve the technical problem of poor cycle performance of the battery caused by gas production of a lithium supplement agent. The positive pole piece comprises a current collector and a first active material layer arranged on the current collector, the first active material layer comprises a first positive active material, a lithium supplement agent and a first conductive agent, and the first conductive agent comprises porous carbon. The lithium supplement agent and the porous carbon are added into the first active material layer of the positive pole piece, and the porous carbon can promote the lithium supplement agent to be dispersed in the first active material layer and improve the porosity of the positive pole piece, so that a large number of lithium ions released by the lithium supplement agent can be conducted through pore channels in the porous carbon; moreover, gas generated by the lithium supplement agent can be led out and released through the pore channels in the porous carbon, so that the damage of the gas generated by the lithium supplement agent to the interface of the positive pole piece is relieved, the transmission efficiency of lithium ions in the positive pole piece is improved, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and specifically to a positive electrode sheet, a method for preparing a positive electrode sheet, and a battery. Background Art

[0002] During the first charge of a lithium-ion battery, the electrolyte will be reduced and decomposed on the surface of the negative electrode to form a solid electrolyte interface (SEI) film. This process consumes a large amount of lithium ions from the positive electrode, resulting in a low initial coulombic efficiency of the lithium-ion battery and reducing the capacity and energy density of the lithium-ion battery. Adding lithium supplements to the electrode materials of lithium-ion batteries can offset lithium loss to a certain extent, thereby improving the energy density of lithium-ion batteries. However, lithium supplements are prone to produce gas during the formation stage of lithium-ion batteries, and the generation of gas will affect the cycle performance of lithium-ion batteries. Summary of the invention

[0003] The embodiments of the present application provide a positive electrode plate and a preparation method thereof, as well as a battery, which can improve the technical problem of poor battery cycle performance caused by gas production by lithium supplement agents.

[0004] In a first aspect, an embodiment of the present application provides a positive electrode sheet, comprising:

[0005] a current collector; and

[0006] A first active material layer is disposed on the current collector, wherein the first active material layer comprises a first positive electrode active material, a lithium supplement and a first conductive agent, wherein the first conductive agent comprises porous carbon.

[0007] In one embodiment, in the first positive electrode active material, the ratio of the porous carbon to the lithium supplement is D, and 0.025≤D≤0.25.

[0008] In one embodiment, the pore size of the pores inside the porous carbon is 300 nm to 600 nm.

[0009] In one embodiment, the D50 particle size of the porous carbon is 25 μm to 50 μm.

[0010] In one embodiment, the D50 particle size of the lithium supplement is 9 μm to 15 μm.

[0011] In one embodiment, the porosity of the porous carbon is 92% to 96%.

[0012] In one embodiment, the density of the porous carbon is 0.4 g / cm 3 ~1.2g / cm 3 .

[0013] In one embodiment, in the first active material layer, the mass percentage of the lithium supplement agent is 0.5% to 3.5%, and the mass percentage of the porous carbon is 0.1% to 0.4%.

[0014] In one embodiment, the lithium supplement comprises Li 5 FeO 4 .

[0015] In one embodiment, the porous carbon includes foamed carbon.

[0016] In one embodiment, the positive electrode plate further includes a second active material layer, the second active material layer is located on a side of the first active material layer away from the current collector, the second active material layer includes a second positive electrode active material and a second conductive agent; the second conductive agent includes single-walled carbon nanotubes.

[0017] In one embodiment, a ratio P of a content percentage of the second conductive agent in the second active material layer to a content percentage of the first conductive agent in the first active material layer is ≤0.79.

[0018] In one embodiment, in the second active material layer, the mass percentage of the single-walled carbon nanotubes is 0.01% to 0.05%.

[0019] In one embodiment, the first conductive agent further comprises at least one of carbon nanotubes, vapor-grown carbon fibers and conductive carbon black.

[0020] In one embodiment, the second conductive agent further includes at least one of conductive carbon black, vapor-grown carbon fiber and multi-walled carbon nanotube.

[0021] In one embodiment, the first active material layer also includes a first binder and a first dispersant. In the first active material layer, the mass percentage of the first active material is 94.5% to 95.5%, the mass percentage of the lithium supplement agent is 0.7% to 3.5%, the mass percentage of the first conductive agent is 0.5% to 1.5%, the mass percentage of the first binder is 1.2% to 2.0%, and the mass percentage of the first dispersant is 0.1% to 0.3%.

[0022] In one embodiment, the second active material layer also includes a second binder and a second dispersant. In the second active material layer, the mass percentage of the second active material is 96.5% to 97.7%, the mass percentage of the second conductive agent is 0.6% to 2.2%, the mass percentage of the second binder is 1.2% to 2.0%, and the mass percentage of the second dispersant is 0.1% to 0.3%.

[0023] In one embodiment, the first positive electrode active material includes lithium iron manganese phosphate; and the second positive electrode active material includes lithium iron manganese phosphate.

[0024] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode sheet, comprising:

[0025] Providing a first slurry, wherein the first slurry comprises a first positive electrode active material, a first conductive agent, a lithium supplement agent and a first solvent, wherein the first conductive agent comprises porous carbon;

[0026] The first slurry is subjected to a film-forming process on a current collector to obtain a first wet film layer, and the first wet film layer is subjected to a drying process to obtain a first active material layer.

[0027] In one embodiment, the preparation process of the first slurry includes: mixing the porous carbon with the lithium supplement agent to obtain a first mixture, and mixing the first mixture with the first positive electrode active material and the first solvent to obtain the first slurry.

[0028] In one embodiment, the method for preparing the positive electrode sheet further includes:

[0029] Providing a second slurry, the second slurry comprising a second positive electrode active material, a second conductive agent and a second solvent, the second conductive agent comprising single-walled carbon nanotubes;

[0030] The second slurry is subjected to a film-forming treatment on a side of the first active material layer away from the current collector to obtain a second wet film layer, and the second wet film layer is subjected to a drying treatment to obtain a second active material layer.

[0031] In one embodiment, the preparation process of the porous carbon includes: adding 0.5wt%-1.5wt% ammonium chloride, 0.5wt%-1.5wt% sodium bicarbonate, and 10wt%-14wt% glucose to 85wt%-89wt deionized water, stirring for 3h to 10h to obtain a second mixture, freeze-drying the second mixture to obtain a white powder, and then calcining the white powder under a protective atmosphere for 20h to 30h to obtain porous carbon.

[0032] In a third aspect, an embodiment of the present application provides a battery, comprising the above-mentioned positive electrode plate; or, the positive electrode plate prepared by the above-mentioned method.

[0033] Beneficial effects of the embodiments of the present application:

[0034] In an embodiment of the present application, the first active material layer of the positive electrode plate includes a first positive electrode active material, a lithium supplement and porous carbon. The porous carbon is a three-dimensional carbon material with a rich pore structure inside. The porous carbon can promote the dispersion of the lithium supplement in the first active material layer and increase the porosity of the positive electrode plate, especially the porosity of the first active material layer. In this way, not only can a large amount of lithium ions released by the lithium supplement be conducted through the pores inside the porous carbon, but the gas generated by the lithium supplement can also be discharged and released through the pores inside the porous carbon, thereby alleviating the damage of the lithium supplement to the interface of the positive electrode plate caused by gas production, improving the efficiency of lithium ion transmission in the positive electrode plate, and improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0036] Figure 1 is a cross-sectional view of a positive electrode sheet provided in an embodiment of the present application;

[0037] Figure 2 It is a flow chart of a method for preparing a positive electrode sheet provided in an embodiment of the present application;

[0038] Figure 3 This is an electron microscope image of the porous carbon provided in Example 1 of the present application. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of this application.

[0040] In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise stated, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device.

[0041] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0042] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or mutual communication; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0043] The terms "comprises," "includes," or any other variation thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements, but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus. In the absence of further limitations, an element defined by the phrase "comprises a ..." does not exclude the presence of additional identical elements in the process, method, article, or apparatus that includes the element.

[0044] In the description of the embodiments of the present application, words such as "example" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "example" or "for example" in the embodiments of the present application is not to be interpreted as being more preferred or having more advantages than another embodiment or design. The use of words such as "example" or "for example" is intended to present relative concepts in a clear manner.

[0045] To facilitate understanding of the scheme of the present application, the spline curves and arrows used in the drawings are explained here: the components indicated by the spline curves without arrows are solid components, that is, components with solid structures; the components indicated by the spline curves with arrows are virtual components, that is, components without solid structures.

[0046] First, see Figure 1 An embodiment of the present application provides a positive electrode plate 10, which is used in a battery, such as a lithium-ion battery.

[0047] Specifically, the positive electrode sheet 10 includes a current collector 1 and a first active material layer 2, and the first active material layer 2 is disposed on the current collector 1. The first active material layer 2 includes a first positive active material, a lithium supplement and a first conductive agent, and the first conductive agent includes porous carbon.

[0048] Lithium replenishers can replenish the irreversible lithium loss of the battery during the first charge and discharge process. However, the lithium replenisher will decompose and produce gases, such as oxygen, during the first charging process (such as the formation stage). The gas production problem of lithium replenishers is a common challenge, but the gas production of different types of lithium replenishers is usually different. For example, lithium iron-rich lithium replenishers will release oxygen during the first charge, causing the ethylene carbonate (EC) in the electrolyte to oxidize and decompose to produce carbon dioxide and water, thereby triggering a series of gas production reactions; binary lithium-containing compound lithium replenishers, such as Li 2 O 2 and Li 2 O will also produce oxygen during the delithiation process; nickel-acid lithium supplements are easy to decompose and produce gas under high voltage; although squarate lithium supplements have environmental stability and process compatibility, their gas production problem still exists. The gas production of lithium supplements can easily cause damage to the electrode interface, thereby slowing down the transfer of lithium ions and ultimately affecting the cycle life of the battery.

[0049] The first active material layer 2 of the positive electrode plate 10 provided in the embodiment of the present application contains a first positive electrode active material, a lithium supplement and porous carbon. The porous carbon is a three-dimensional carbon material with a rich pore structure inside. The porous carbon can promote the dispersion of the lithium supplement in the first active material layer 2 and increase the porosity of the positive electrode plate 10, especially the porosity of the first active material layer 2. In this way, not only can a large amount of lithium ions released by the lithium supplement be conducted through the pores inside the porous carbon, but the gas generated by the lithium supplement can also be discharged and released through the pores inside the porous carbon, thereby alleviating the damage of the gas generated by the lithium supplement to the interface of the positive electrode plate 10, improving the efficiency of lithium ion transmission in the positive electrode plate 10, and improving the cycle performance of the battery.

[0050] In some embodiments, the first positive electrode active material includes lithium manganese iron phosphate (LMFP). The chemical formula of lithium manganese iron phosphate is LiFe a Mn b PO 4 , 0<a<1, 0<b<1. As an example, a is 0.001, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 0.999; b is 0.001, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 0.999.

[0051] Lithium manganese iron phosphate (LMFP) is a positive electrode active material obtained by adding manganese to lithium iron phosphate (LFP). The voltage of lithium manganese iron phosphate can be increased by increasing the content of manganese, making up for the deficiency of low energy density caused by low voltage of lithium iron phosphate. However, excessive manganese content in lithium manganese iron phosphate will cause too high a proportion of manganese dissolution, thereby destroying the solid solution structure and reducing the conductivity, rate capability and discharge efficiency of the battery. In the embodiment of the present application, the electrochemical properties of lithium manganese iron phosphate can be improved by adding a lithium supplement to the first active material layer 2, thereby improving the capacity, cycle life and energy density of the battery.

[0052] In some embodiments, the lithium supplement includes lithium ferrite (LFO), the chemical formula of which is Li 5 FeO 4 . Lithium ferrite is a lithium metal oxide with an inverse fluorite structure. It has a relatively high specific capacity, and the theoretical gram capacity can reach 700mAh / g. It is an ideal pre-embedded lithium additive. For example, in the LMFP battery system, when the addition amount of lithium ferrite is 2wt%, the energy density can be increased by 5%, and the cycle can be increased by 800 cycles at 25°C. However, lithium ferrite produces serious gas during the formation stage. In an embodiment of the present application, by mixing lithium ferrite with porous carbon and adding it to the first active material layer 2, the porous carbon can adapt to the characteristics of lithium ferrite and assist the gas generated by lithium ferrite to dissipate, thereby reducing damage to the interface of the positive electrode plate 10, improving the efficiency of lithium ion transmission in the positive electrode plate 10, and improving the cycle performance of the battery.

[0053] In some embodiments, the porous carbon includes foamed carbon, which is also called carbon foam, and has the characteristics of high conductivity, low density, chemical / thermal inertness, etc., which is conducive to further improving the electrochemical performance of the battery.

[0054] In some embodiments, the preparation process of porous carbon includes: adding 0.5wt%-1.5wt% ammonium chloride, 0.5wt%-1.5wt% sodium bicarbonate, and 10wt%-14wt% glucose to 85wt%-89wt% deionized water and stirring for 3h to 10h to obtain a second mixture, freeze-drying the second mixture to obtain a white powder, and then calcining the white powder under a protective atmosphere for 20h to 30h to obtain porous carbon.

[0055] In some embodiments, in the first active material layer 2, the ratio of porous carbon to lithium supplement is D, 0.025≤D≤0.25. It can be understood that the higher the content of porous carbon, the larger D is, and the easier it is to extract the gas generated by the lithium supplement. However, too high a content of porous carbon is likely to affect the energy density of the battery; the lower the content of porous carbon, the smaller D is, and too low a content of porous carbon will affect the rate at which the gas generated by the lithium supplement escapes, which will not effectively alleviate the damage to the interface of the positive electrode sheet 10. Within this range, porous carbon and lithium supplements can effectively cooperate, so that the battery has both better energy density and cycle life. As an example, D is 0.025, 0.05, 0.075, 0.1, 0.125, 0.15, 0.175, 0.2, 0.225 or 0.25.

[0056] In some embodiments, in the first active material layer, the mass percentage of the lithium supplement agent is 0.5% to 3.5%, and the mass percentage of the porous carbon is 0.1% to 0.4%. As an example, in the first active material layer, the mass percentage of the lithium supplement agent is 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0% or 3.5%, and the mass percentage of the porous carbon is 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35% or 0.4%.

[0057] In some embodiments, the pore size of the pores inside the porous carbon is 300nm to 600nm. The pore size of the pores inside the porous carbon should not be too small, otherwise it will affect the rate of gas extraction, but too large a pore size will cause the mechanical strength of the porous carbon to decrease, which is not conducive to the manufacture of the positive electrode plate 10, and the structure of the porous carbon is also easily destroyed during the cycle, so that the gas conduction cannot be achieved well. As an example, the pore size of the pores inside the porous carbon is 300nm, 350nm, 400nm, 450nm, 500nm, 550nm or 600nm. Optionally, inside the porous carbon, the pores are arranged closely.

[0058] In some embodiments, the D50 particle size of the porous carbon is 25 μm to 50 μm. The particle size of the porous carbon should not be too large, otherwise it will affect the dispersion effect of the porous carbon in the first active material layer 2. Of course, the particle size of the porous carbon should not be too small, otherwise it will be difficult to enlarge the pore size of the pores inside the porous carbon. As an example, the D50 particle size of the porous carbon is 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm.

[0059] In some embodiments, the D50 particle size of the lithium supplement is 9 μm to 15 μm. The particle size of the lithium supplement should not be too large, otherwise it will affect the dispersion effect of the lithium supplement in the first active material layer 2. Of course, the particle size of the lithium supplement should not be too small, otherwise it will reduce the stability of the lithium supplement, especially when the lithium supplement includes Li 5 FeO4 When Li 5 FeO 4 It not only has the characteristics of strong water absorption, but also is easy to decompose when exposed to air for a long time. As an example, the D50 particle size of the lithium supplement is 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm.

[0060] In some embodiments, the porosity of the porous carbon is 92% to 96%. Increasing the porosity of the porous carbon is beneficial to increasing the rate at which the gas generated by the lithium supplement is released, further alleviating damage to the interface of the positive electrode sheet 10. As an example, the porosity of the porous carbon is 92%, 93%, 94%, 95% or 96%.

[0061] In some embodiments, the density of the porous carbon is 0.4 g / cm 3 ~1.2g / cm 3 As an example, the density of porous carbon is 0.4 g / cm 3 , 0.5g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 or 1.2g / cm 3 .

[0062] In some embodiments, the first conductive agent also includes at least one of conductive carbon black, carbon nanotubes (CNTs) and vapor grown carbon fibers (VGCF). As an example, the conductive carbon black includes at least one of acetylene black, Super P (SP) and Ketjen black. As an example, the carbon nanotubes include at least one of single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs). Conductive carbon black has good electrical conductivity, and conductive carbon black has a smaller particle size and a larger specific surface area, which can be better dispersed in the matrix material to improve the electrical conductivity. As a fibrous conductive agent, VGCF can improve the conductivity and charge and discharge rate of lithium batteries, and VGCF has corrosion resistance and oxidation resistance, and can maintain stable electrical conductivity in harsh environments. Carbon nanotubes are one-dimensional tubular structures, and carbon rings can form a conjugated effect. A small amount of addition can form a conductive network that fully connects active substances, which is beneficial to improving the capacity and cycle stability of the battery. Carbon nanotubes have a double electrical layer effect, which is beneficial to improving the high-rate charge and discharge performance of the battery. In addition, carbon nanotubes also have good thermal conductivity, which helps the heat dissipation of the battery and reduces internal polarization. The electrochemical performance of the battery can be further improved through the coordination of a variety of conductive agents.

[0063] In some embodiments, the first active material layer 2 also includes a first binder and a first dispersant. In the first active material layer 2, the mass percentage of the first active material is 94.5% to 95.5%, the mass percentage of the lithium supplement is 0.7% to 3.5%, the mass percentage of the first conductive agent is 0.5% to 1.5%, the mass percentage of the first binder is 1.2% to 2.0%, and the mass percentage of the first dispersant is 0.1% to 0.3%. As an example, in the first active material layer 2, the mass percentage of the first active material is 94.5%, 94.7%, 94.9%, 95.1%, 95.3% or 95.5%; the mass percentage of the lithium supplement is 0.7%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0% or 3.5%; the mass percentage of the first conductive agent is 0.5%, 0.7%, 0.9%, 1.1%, 1.3% or 1.5%; the mass percentage of the first binder is 1.2%, 1.4%, 1.6%, 1.8% or 2.0%; the mass percentage of the first dispersant is 0.1%, 0.15%, 0.2%, 0.25% or 0.3%.

[0064] In some embodiments, the current collector 11 may be aluminum foil, carbon-coated aluminum foil, safety-primed aluminum foil, etched aluminum foil or aluminum mesh. The thickness of the current collector 11 may be 5 μm to 20 μm, for example 5 μm, 10 μm, 15 μm or 20 μm.

[0065] In some embodiments, a first active material layer 2 is disposed on one surface of the current collector 11 .

[0066] In some embodiments, the first active material layer 2 is disposed on both opposite sides of the current collector 11 .

[0067] In some embodiments, see Figure 1 The positive electrode sheet 10 further includes a second active material layer 3, which is located on a side of the first active material layer 2 away from the current collector 1. The second active material layer 3 includes a second positive active material and a second conductive agent; the second conductive agent includes single-walled carbon nanotubes.

[0068] Single-walled carbon nanotubes (SWCNTs) are made of a layer of rolled carbon atoms, with a tubular structure and a high length-to-diameter ratio (aspect ratio). It is precisely because of the high aspect ratio of single-walled carbon nanotubes that their electron transport is more direct and efficient, and they can form a three-dimensional conductive network at a very low addition amount.

[0069] By designing the active material layer in the positive electrode plate 10 in layers, the active material layer is configured to include a first active material layer 2 and a second active material layer 3 that are stacked, wherein the first active material layer 2 includes a lithium supplement and porous carbon, and the second active material layer 3 includes single-walled carbon nanotubes. The single-walled carbon nanotubes can construct a more uniform three-dimensional conductive network in the second active material layer 3, and the porous carbon can promote the rapid conduction of lithium ions released by the lithium supplement in the first active material layer 2 to the second active material layer 3. The two cooperate with each other, making the positive electrode plate 10 more stable during high-rate and high-temperature charging and discharging.

[0070] In addition, by shielding the first active material layer 2 with the second active material layer 3, water vapor can be effectively isolated, thereby reducing the risk of inactivation of the lithium supplement.

[0071] In some embodiments, the type of the second positive electrode active material is the same as the type of the first positive electrode active material. Of course, in other embodiments, the type of the second positive electrode active material may be different from the type of the first positive electrode active material.

[0072] In some embodiments, the second positive electrode active material includes lithium manganese iron phosphate (LMFP). Due to the presence of lithium manganese iron phosphate, the second active material layer 3 is prone to cracking, resulting in the presence of cracks. In addition to being able to effectively construct a three-dimensional conductive network, the single-walled carbon nanotubes also have the characteristics of good elasticity and high mechanical properties. The presence of the single-walled carbon nanotubes can make the second active material layer 3 more flexible, and can be better bent, twisted or kinked, alleviate the generation of cracks, and improve the peeling force.

[0073] In some embodiments, the second conductive agent also includes at least one of vapor-grown carbon fiber, conductive carbon black, and multi-walled carbon nanotubes. The electrochemical performance of the battery can be further improved by the coordination of multiple conductive agents.

[0074] In some embodiments, the mass percentage of the single-walled carbon nanotubes in the second active material layer 3 is 0.01% to 0.05%. As an example, the mass percentage of the single-walled carbon nanotubes in the second active material layer 3 is 0.01%, 0.02%, 0.03%, 0.04% or 0.05%.

[0075] In some embodiments, the ratio P of the percentage of the second conductive agent in the second active material layer 3 to the percentage of the first conductive agent in the first active material layer 2 is ≤ 0.79. It can be understood that the percentage of the second conductive agent in the second active material layer 3 is less than the percentage of the first conductive agent in the first active material layer 2. As an example, the ratio P is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7 or 0.79.

[0076] In some embodiments, the second active material layer 3 also includes a second binder and a second dispersant. In the second active material layer 3, the mass percentage of the second active material is 96.5% to 97.7%, the mass percentage of the second conductive agent is 0.6% to 2.2%, the mass percentage of the second binder is 1.2% to 2.0%, and the mass percentage of the second dispersant is 0.1% to 0.3%. As an example, in the second active material layer 3, the mass percentage of the second active material is 96.5%, 96.7%, 96.9%, 97.1%, 97.3%, 97.5% or 97.7%; the mass percentage of the second conductive agent is 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0% or 2.2%; the mass percentage of the second binder is 1.2%, 1.4%, 1.6%, 1.8% or 2.0%; the mass percentage of the second dispersant is 0.1%, 0.15%, 0.2%, 0.25% or 0.3%.

[0077] It should be noted here that the second binder may be the same as or different from the first binder; the second dispersant may be the same as or different from the first dispersant.

[0078] In some embodiments, the first binder includes at least one of polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), and polyvinyl alcohol (PVA).

[0079] In some embodiments, the second binder includes at least one of polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), and polyvinyl alcohol (PVA).

[0080] In some embodiments, the first dispersant includes at least one of anhydrides, polyvinyl pyrrolidone, sulfate ester salts, poly(N-vinylacetamide), polyvinyl alcohol, sulfonates, and polyethylene glycol.

[0081] In some embodiments, the second dispersant includes at least one of anhydrides, polyvinyl pyrrolidone, sulfate ester salts, poly(N-vinylacetamide), polyvinyl alcohol, sulfonates, and polyethylene glycol.

[0082] Second, see Figure 2 The present application embodiment provides a method for preparing a positive electrode sheet, comprising:

[0083] S1. providing a first slurry, wherein the first slurry comprises a first positive electrode active material, a first conductive agent, a lithium supplement agent and a first solvent, wherein the first conductive agent comprises porous carbon;

[0084] S2. Performing a film-forming process on the first slurry on the current collector to obtain a first wet film layer, and performing a drying process on the first wet film layer to obtain a first active material layer.

[0085] In some embodiments, see Figure 2 , the method for preparing the positive electrode sheet also includes:

[0086] S3, providing a second slurry, wherein the second slurry comprises a second positive electrode active material, a second conductive agent and a second solvent, wherein the second conductive agent comprises single-walled carbon nanotubes;

[0087] S4, performing a film-forming treatment on the second slurry on a side of the first active material layer away from the current collector to obtain a second wet film layer, and performing a drying treatment on the second wet film layer to obtain a second active material layer.

[0088] Optionally, the film forming process is a coating process, and the coating process includes but is not limited to at least one of gravure coating, micro gravure coating, spray coating and electrostatic spinning technology. The first solvent and the second solvent include N-methylpyrrolidone (NMP).

[0089] In some embodiments, the preparation process of the first slurry includes:

[0090] S11, mixing the porous carbon and the lithium supplement agent to obtain a first mixture;

[0091] S12, mixing the first mixture with a first positive electrode active material and a first solvent to obtain a first slurry.

[0092] By mixing the porous carbon with the lithium supplement agent first and then with other materials, the porous carbon and the lithium supplement agent can be brought closer together in the first active material layer, making it easier for the porous carbon to extract the gas generated by the lithium supplement agent.

[0093] In some embodiments, the preparation process of porous carbon includes: adding 0.5wt%-1.5wt% ammonium chloride, 0.5wt%-1.5wt% sodium bicarbonate, and 10wt%-14wt% glucose to 85wt%-89wt% deionized water and stirring for 3h to 10h to obtain a second mixture, freeze-drying the second mixture to obtain a white powder, and then calcining the white powder under a protective atmosphere for 20h to 30h to obtain porous carbon. As an example, the amount of ammonium chloride used is 0.5wt%, 0.7wt%, 0.9wt%, 1.1wt%, 1.3wt% or 1.5wt%; the amount of sodium bicarbonate used is 0.5wt%, 0.7wt%, 0.9wt%, 1.1wt%, 1.3wt% or 1.5wt%; the amount of glucose used is 10wt%, 11wt%, 12wt%, 13wt% or 14wt%; the amount of deionized water used is 85wt%, 86wt%, 87wt%, 88wt% or 89%wt.

[0094] In some embodiments, the method for preparing the positive electrode sheet is used to prepare the positive electrode sheet 10 provided in the first aspect.

[0095] In a third aspect, an embodiment of the present application further provides a battery, comprising the above-mentioned positive electrode plate 10; or, the positive electrode plate prepared by the above-mentioned method.

[0096] In some embodiments, the battery is a lithium ion battery.

[0097] The following is a description with reference to specific embodiments.

[0098] Example 1

[0099] S0. Preparation of porous carbon: 0.5 wt% ammonium chloride, 0.5 wt% sodium bicarbonate, and 10 wt% glucose were added to 89 wt% deionized water, stirred for 6 h, freeze-dried to obtain a white powder, and then the white powder was calcined under argon for 24 h to obtain porous carbon. The electron microscope image of the porous carbon is as follows: Figure 3 shown.

[0100] S1. Prepare the positive electrode: Apply the positive electrode slurry to the carbon-coated aluminum foil current collector by double-layer coating, dry it, cold press it, and cut it into pieces. The formula of the positive electrode slurry is:

[0101] a. Upper slurry: LMFP (LiFe 0.5 Mn 0.5 PO 4 , 97.5wt%), SP (0.35wt%), MWCNT (0.2wt%), SWCNT (0.05wt%), PVDF (1.7wt%), dispersant (0.2wt%).

[0102] b. Lower layer slurry: LMFP (94.9wt%), LFO (2wt%), SP (0.6wt%), MWCNT (0.5wt%), porous carbon (0.1wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0103] S2. Preparation of negative electrode: Apply the negative electrode slurry to the copper foil current collector by single-layer coating, dry it, cold press it, and cut it into pieces. The formula of the negative electrode slurry is: graphite, SP, VGCF, CMC, SBR, wherein graphite: SP: VGCF: CMC: SBR = 96.7: 0.2: 0.4: 1.5: 1.2 (mass ratio).

[0104] S3. Prepare the battery: assemble the positive and negative pole pieces into a core pack by stacking them, and then perform vacuum baking after assembly. After baking, inject the electrolyte after the moisture content is qualified. The electrolyte is 1M LiPF 6(EC:DEC:DMC=1:1:1, volume ratio), after the liquid injection is completed, let it stand for 24 hours to evolve into capacity, and after the capacity is completed, vacuum packaging is carried out and the soft-pack battery cell is offline.

[0105] Example 2

[0106] The difference from Example 1 is that in the positive electrode slurry formula, the formula of the upper slurry and the lower slurry are different, wherein:

[0107] a. Upper slurry: LMFP (97.0wt%), SP (0.6wt%), MWCNT (0.45wt%), SWCNT (0.05wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0108] b. Lower layer slurry: LMFP (94.7wt%), LFO (2wt%), SP (0.7wt%), MWCNT (0.55wt%), porous carbon (0.15wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0109] Example 3

[0110] The difference from Example 1 is that in the positive electrode slurry formula, the formula of the upper slurry and the lower slurry are different, wherein:

[0111] a. Upper slurry: LMFP (97.5wt%), SP (0.35wt%), MWCNT (0.2wt%), SWCNT (0.05wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0112] b. Lower layer slurry: LMFP (94.9wt%), LFO (2wt%), SP (0.55wt%), MWCNT (0.45wt%), porous carbon (0.2wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0113] Example 4

[0114] The difference from Example 1 is that in the positive electrode slurry formula, the formula of the upper slurry and the lower slurry are different, wherein:

[0115] a. Upper slurry: LMFP (97.5wt%), SP (0.35wt%), MWCNT (0.2wt%), SWCNT (0.05wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0116] b. Lower layer slurry: LMFP (94.9wt%), LFO (2wt%), SP (0.45wt%), MWCNT (0.35wt%), porous carbon (0.4wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0117] Example 5

[0118] The difference from Example 1 is that in the positive electrode slurry formula, the formula of the upper slurry and the lower slurry are different, wherein:

[0119] a. Upper slurry: LMFP (97.5wt%), SP (0.35wt%), MWCNT (0.2wt%), SWCNT (0.05wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0120] b. Lower layer slurry: LMFP (94.9wt%), LFO (2wt%), SP (0.4wt%), MWCNT (0.3wt%), porous carbon (0.5wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0121] Example 6

[0122] The difference from Example 1 is that in the positive electrode slurry formula, the formula of the upper slurry and the lower slurry are different, wherein:

[0123] a. Upper slurry: LMFP (97.5wt%), SP (0.35wt%), MWCNT (0.2wt%), SWCNT (0.05wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0124] b. Lower layer slurry: LMFP (94.9wt%), LFO (2wt%), SP (0.625wt%), MWCNT (0.525wt%), porous carbon (0.05wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0125] Example 7

[0126] The difference from Example 1 is:

[0127] S1. Preparation of positive electrode: The positive electrode slurry is applied to the carbon-coated aluminum foil current collector by single-layer coating, and then cold pressed and cut into pieces after drying. The positive electrode slurry formula is: LMFP (94.9wt%), LFO (2wt%), SP (0.6wt%), MWCNT (0.5wt%), porous carbon (0.1wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0128] Comparative Example 1

[0129] The difference from Example 1 is that in the positive electrode slurry formula, the formula of the upper slurry and the lower slurry are different, wherein:

[0130] a. Upper slurry: LMFP (97.5wt%), SP (0.35wt%), MWCNT (0.2wt%), SWCNT (0.05wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0131] b. Lower layer slurry: LMFP (94.9wt%), LFO (2wt%), SP (0.7wt%), MWCNT (0.5wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0132] Comparative Example 2

[0133] The difference from Example 1 is:

[0134] S1. Preparation of positive electrode: Apply the positive electrode slurry to the carbon-coated aluminum foil current collector by single-layer coating, dry it, cold press it, and cut it into pieces. The positive electrode slurry formula is: LMFP (97.5wt%), SP (0.35wt%), MWCNT (0.2wt%), SWCNT (0.05wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0135] Comparative Example 3

[0136] The difference from Example 7 is that the positive electrode slurry formula is: LMFP (94.9wt%), LFO (2wt%), SP (0.7wt%), MWCNT (0.5wt%), PVDF (1.7wt%), and dispersant (0.2wt%).

[0137] The parameters of each embodiment and comparative example are shown in Table 1:

[0138] Table 1

[0139]

[0140] 1. The batteries prepared in the examples and comparative examples were tested as follows:

[0141] 1.1. Capacity retention rate test: At 25°C, the battery was subjected to a 1C / 1C cycle test. The capacity retention rate was calculated by dividing the capacity after 600 cycles by the initial capacity to obtain the capacity retention rate after the cycle. The test results are recorded in Table 2.

[0142] 1.2. DC internal resistance (DCR) growth rate test: DCR test was performed at 1C@10s 70% SOC DCR; at 25°C, the battery was subjected to 1C / 1C cycle test, and the DCR growth rate was calculated by dividing the difference between the DCR after 600 cycles and the initial DCR by the initial DCR to obtain the DCR growth rate after the cycle. The test results are recorded in Table 2.

[0143] 1.2. Please see Table 2 for test results.

[0144] Table 2

[0145] Group Capacity retention rate / % DCR growth rate / % Example 1 96.88 10.01 Example 2 96.41 9.89 Example 3 96.91 9.91 Example 4 96.90 9.87 Example 5 96.71 10.2 Example 6 96.51 10.31 Example 7 96.01 11.01 Comparative Example 1 95.89 11.23 Comparative Example 2 95.31 11.22 Comparative Example 3 95.13 11.68

[0146] 2. Observe the number of cracks on the surface of the positive electrode sheets prepared in each embodiment and comparative example, and the results are recorded in Table 3:

[0147] Table 3

[0148] Group Crack quantity / crack quantity per 1m of positive electrode sheet Example 1 0 Example 2 0 Example 3 1 Example 4 0 Example 5 0 Example 6 1 Example 7 5 Comparative Example 1 1 Comparative Example 2 0 Comparative Example 3 7

[0149] From the data in Table 3 and Table 4, we can see that:

[0150] The capacity retention rates of the batteries provided in Examples 1 to 7 are all greater than the capacity retention rates of the batteries provided in Comparative Examples 1 to 3, but the DCR growth rates of the batteries provided in Examples 1 to 7 are all less than the DCR growth rates of the batteries provided in Comparative Examples 1 to 3, which indicates that the electrochemical performance of the batteries provided in Examples 1 to 7 is better.

[0151] The number of cracks on the surface of the positive electrode sheets provided by Examples 1 to 6, and Comparative Examples 1 and 2 is significantly less than the number of cracks on the surface of the positive electrode sheets provided by Example 7 and Comparative Example 3, which indicates that adding single-walled carbon nanotubes to the active material layer containing LMFP can effectively improve the flexibility of the active material layer and reduce the occurrence of cracks.

[0152] By comparing the test results of the batteries provided by Example 6, Example 1, and Example 3 to Example 5 in Table 3, it can be seen that although the total amount of the conductive agent is the same, as the content of porous carbon in the conductive agent increases, the capacity retention first increases and then slightly decreases, and the DCR growth rate first decreases and then increases. This is because increasing the content of porous carbon can promote the conduction of lithium ions in the electrode and accelerate gas conduction, but if the content of porous carbon is too large, it will become redundant and will also cause the content of other active components to decrease, thereby reducing the performance of the battery.

[0153] By comparing the test results of the batteries provided in Example 1 and Comparative Example 1, it can be seen that in Comparative Example 1, the porous carbon is replaced with SP, and the capacity retention rate of the battery provided in Comparative Example 1 is reduced, and the DCR growth rate is increased. This is because the gas generated by the decomposition of the lithium replenisher inside the positive electrode plate in Comparative Example 1 is not effectively discharged, resulting in interface damage to the positive electrode plate, which increases the internal resistance of the battery and reduces the cycle performance.

[0154] By comparing the test results of the batteries provided in Example 1 and Comparative Example 2, it can be seen that the active material layer in the positive electrode plate in Comparative Example 2 is a single-layer structure, which cancels the active material layer (i.e., the lower structure) containing the lithium supplement and porous carbon in Example 1. Although there are few cracks on the surface of the positive electrode plate, in the absence of lithium supplement, the electronic conductivity and lithium ion diffusion rate of LMFP are poor, which leads to an increase in the internal resistance of the battery and a decrease in the cycle performance.

[0155] By comparing the test results of the batteries provided in Example 1 and Example 7, it can be seen that the active material layer in the positive electrode plate in Example 7 is a single-layer structure, which eliminates the active material layer (i.e., the upper structure) containing single-walled carbon nanotubes in Example 1. In the absence of the active material layer, the bending performance of the positive electrode plate is reduced, resulting in an increase in cracks on the surface of the positive electrode plate (as can be seen in Table 4), thereby increasing the internal resistance of the battery and reducing the cycle performance.

[0156] By comparing the test results of the batteries provided in Example 7 and Comparative Example 3, it can be seen that the active material layer in the positive electrode plate in Comparative Example 3 is a single-layer structure, which cancels the active material layer containing single-walled carbon nanotubes in Example 1 (i.e., the upper structure), and the porous carbon is replaced by SP in Comparative Example 3. In the absence of lithium supplementation and upper structure coverage, the number of cracks on the surface of the positive electrode plate increases significantly (as can be seen from Table 4), the internal resistance of the battery increases significantly, and the cycle performance decreases significantly. Compared with Comparative Examples 1 and 2, the performance deterioration is more obvious.

[0157] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of ​​the present application. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A positive electrode sheet, characterized in that: include: current collector; and A first active material layer is disposed on the current collector, wherein the first active material layer comprises a first positive electrode active material, a lithium supplement and a first conductive agent, wherein the first conductive agent comprises porous carbon.

2. The positive electrode sheet according to claim 1, characterized in that: In the first positive electrode active material, the ratio of the porous carbon to the lithium supplement agent is D, and 0.025≤D≤0.

25.

3. The positive electrode sheet according to claim 1, characterized in that: The pore size of the pores inside the porous carbon is 300nm to 600nm; and / or, the D50 particle size of the porous carbon is 25μm to 50μm; and / or, the D50 particle size of the lithium supplement is 9μm to 15μm; and / or, the porosity of the porous carbon is 92% to 96%; and / or, the density of the porous carbon is 0.4g / cm 3 ~1.2g / cm 3 .

4. The positive electrode sheet according to claim 1, characterized in that: In the first active material layer, the mass percentage of the lithium supplement agent is 0.5% to 3.5%, and the mass percentage of the porous carbon is 0.1% to 0.4%.

5. The positive electrode sheet according to claim 1, characterized in that: The lithium supplement includes Li5FeO4; and / or the porous carbon includes foamed carbon.

6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The positive electrode sheet also includes a second active material layer, which is located on a side of the first active material layer away from the current collector. The second active material layer includes a second positive electrode active material and a second conductive agent; the second conductive agent includes single-walled carbon nanotubes.

7. The positive electrode sheet according to claim 6, characterized in that: The ratio P of the percentage of the second conductive agent in the second active material layer to the percentage of the first conductive agent in the first active material layer is ≤0.79; and / or, in the second active material layer, the mass percentage of the single-walled carbon nanotubes is 0.01% to 0.05%.

8. The positive electrode sheet according to claim 6, characterized in that: The first conductive agent further includes at least one of carbon nanotubes, vapor-grown carbon fibers and conductive carbon black; and / or the second conductive agent further includes at least one of conductive carbon black, vapor-grown carbon fibers and multi-walled carbon nanotubes.

9. The positive electrode sheet according to claim 6, characterized in that: The first active material layer further includes a first binder and a first dispersant. In the first active material layer, the mass percentage of the first active material is 94.5% to 95.5%, the mass percentage of the lithium supplement is 0.7% to 3.5%, the mass percentage of the first conductive agent is 0.5% to 1.5%, the mass percentage of the first binder is 1.2% to 2.0%, and the mass percentage of the first dispersant is 0.1% to 0.3%; and / or, The second active material layer also includes a second binder and a second dispersant. In the second active material layer, the mass percentage of the second active material is 96.5% to 97.7%, the mass percentage of the second conductive agent is 0.6% to 2.2%, the mass percentage of the second binder is 1.2% to 2.0%, and the mass percentage of the second dispersant is 0.1% to 0.3%.

10. The positive electrode sheet according to claim 6, characterized in that: The first positive electrode active material includes lithium iron manganese phosphate; the second positive electrode active material includes lithium iron manganese phosphate.

11. A method for preparing a positive electrode sheet, characterized in that: include: Providing a first slurry, wherein the first slurry comprises a first positive electrode active material, a first conductive agent, a lithium supplement agent and a first solvent, wherein the first conductive agent comprises porous carbon; The first slurry is subjected to a film-forming process on a current collector to obtain a first wet film layer, and the first wet film layer is subjected to a drying process to obtain a first active material layer.

12. The method for preparing a positive electrode sheet according to claim 11, characterized in that: The preparation process of the first slurry includes: mixing the porous carbon with the lithium supplement agent to obtain a first mixture, and mixing the first mixture with the first positive electrode active material and the first solvent to obtain the first slurry.

13. The method for preparing a positive electrode sheet according to claim 11, characterized in that: The method for preparing the positive electrode sheet also includes: Providing a second slurry, the second slurry comprising a second positive electrode active material, a second conductive agent and a second solvent, the second conductive agent comprising single-walled carbon nanotubes; The second slurry is subjected to a film-forming treatment on a side of the first active material layer away from the current collector to obtain a second wet film layer, and the second wet film layer is subjected to a drying treatment to obtain a second active material layer.

14. The method for preparing a positive electrode sheet according to claim 11, characterized in that: The preparation process of the porous carbon includes: adding 0.5wt%-1.5wt% ammonium chloride, 0.5wt%-1.5wt% sodium bicarbonate, and 10wt%-14wt% glucose into 85wt%-89wt% deionized water, stirring for 3h to 10h to obtain a second mixture, freeze-drying the second mixture to obtain a white powder, and then calcining the white powder under a protective atmosphere for 20h to 30h to obtain porous carbon.

15. A battery, characterized in that: It comprises the positive electrode sheet as described in any one of claims 1 to 10; or, the positive electrode sheet prepared by the method as described in any one of claims 11 to 14.

Citation Information

Cited By

  • Battery cell, battery device and electric device

    CN119993981A

  • Battery cells, battery devices, and power-consuming devices

    CN119993981B

  • Positive electrode sheet, secondary battery, and electric device

    WO2026002262A1